Lessons learned from environmental risk assessment within the framework of Seveso Directive in Czech Republic and Italy. (September 2017) - Sikorova, Katerina; Bernatik, Ales; Lunghi, Erika; Fabiano, Bruno
Abstract: Major environmental accidents prevention and risk minimization are currently two the most challenging research issues within the broad framework of sustainable development. This consideration applies to a wide range of process establishments, where the handling and production of dangerous chemicals poses a real threat for the environment for short and long term. Currently, any new establishment with the potential to create a major accident has to be carefully evaluated at the design stage and according to the changes introduced by the Seveso III Directive concerning its scope, particularly regarding substances with acute toxicity, as well as the increased requirements for public information and external emergency. This paper aims at providing experiences, knowledge, as well as new approaches to the prevention of major accidents, with impacts on the environment, driven by the implementation of the new Seveso Directive. We firstly present a statistical analysis on environmental accidents in two European Countries where completely different watery surface and sea coastline extension cause different patterns and impact in case of an accident. Subsequently, we develop a methodological approach within the Seveso framework, focused on environmental risk assessment. At last, the recognized selected methodologies are illustrated by a practical Czech case-study and the findings are used to make recommendations concerning the need of considering safety barriers and technical measures for equally protecting human health and the environment. Highlights: Major accident prevention in the Czech Republic. Implementation of Seveso Directives in the Czech Republic. Experience with environmental risk assessment in Seveso establishments. Comparison of methods H&V Index and Environment Accident Index. Case study of environmental risk assessment of ammonia water storage.